Analisis Perilaku Konsumen Dalam Memilih Warung Kopi Di Kecamatan Percut Sei Tuan - Syahputra, Friady Eko; Lubis, Zulkarnain (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
This literature review research aims to analyze consumer behavior in choosing a coffee shop in Percut Sei Tuan District, Deli Serdang Regency. Public consumption of processed coffee products in the last decade has grown rapidly almost in all corners of the world. Along with the rapid development of the coffee industry in Indonesia, especially in the Percut Sei Tuan District area, coffee shops have become popular places to gather and enjoy coffee. In this study, the research method used is a literature review, namely a method carried out by collecting, analyzing, and synthesizing various sources of literature that are relevant to the research topic. Consumer behavior as a process of evaluating, obtaining, using or being able to use goods and services. The results of the study show that consumers in Percut Sei Tuan District prefer coffee shops that offer a comfortable atmosphere, complete facilities, strategic locations with large parking lots, good and authentic product quality, friendly, good, and fast service quality, social from friends is also important, and affordable coffee prices are included in consumer decisions in choosing a coffee shop..